2014
DOI: 10.1007/s11356-014-2528-1
|View full text |Cite
|
Sign up to set email alerts
|

Does energy consumption contribute to environmental pollutants? evidence from SAARC countries

Abstract: The objective of the study is to examine the causal relationship between energy consumption and environmental pollutants in selected South Asian Association for Regional Cooperation (SAARC) countries, namely, Bangladesh, India, Nepal, Pakistan, and Srilanka, over the period of 1975-2011. The results indicate that energy consumption acts as an important driver to increase environmental pollutants in SAARC countries. Granger causality runs from energy consumption to environmental pollutants, but not vice versa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…Sajjad et al (2014) indicated climatic threats to international tourism and stress the need to mitigate climatic factors to attract foreign tourists for supporting ecotourism global agenda. Akhmat et al (2014c) in another study confirmed the variability in environmental pollutants due to the conventional usage of energy sources that alter the environment in a form to increase extreme temperature and precipitation rate in SAARC countries. Mudakkar et al (2013) supported the nuclear energy demand that derives industrial share to GDP and resources of freshwater on the cost of CO 2 emissions in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 69%
“…Sajjad et al (2014) indicated climatic threats to international tourism and stress the need to mitigate climatic factors to attract foreign tourists for supporting ecotourism global agenda. Akhmat et al (2014c) in another study confirmed the variability in environmental pollutants due to the conventional usage of energy sources that alter the environment in a form to increase extreme temperature and precipitation rate in SAARC countries. Mudakkar et al (2013) supported the nuclear energy demand that derives industrial share to GDP and resources of freshwater on the cost of CO 2 emissions in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 69%
“…Later, Levin et al (2002) develops a panel unit root test by pooling the cross section that allows trend and intercept coefficients to freely move across the cross sections and generated pooled t-statistics. hence, Levin-Lin-Chu (llc) unit root test provides better approximation results as compare to common panel unit root tests ( (Niu et al, 2011); (Akhmat et al, 2014). LLC test suggests the following hypothesis.…”
Section: Methodology and Data 31 Methodology 311 Levine-lin-chu mentioning
confidence: 99%
“…Akhmat et al reported that energy consumption has adverse effects on the environment through the increase in carbon dioxide emissions in SAARC countries. Moreover, in a multivariate framework, Shahbaz et al assert that FDI accelerates energy consumption and economic growth and consequently deteriorates the environment of low and middle income countries.…”
Section: Literature Reviewmentioning
confidence: 99%